DPOAEs in infants developmentally exposed to PCBs show two differently time spaced exposure sensitive windows. (October 2016) - Koštiaková, Vladimíra; Moleti, Arturo; Wimmerová, Soňa; Jusko, Todd A.; Palkovičová Murínová, Ľubica; Sisto, Renata; Richterová, Denisa; Kováč, Ján; Čonka, Kamil; Patayová, Henrieta; Tihányi, Juraj; Trnovec, Tomáš
Abstract: The study aim was to identify the timing of sensitive windows for ototoxicity related to perinatal exposure to PCBs. A total of 351 and 214 children from a birth cohort in eastern Slovakia underwent otoacoustic testing at 45 and 72 months, respectively, and distortion product otoacoustic emissions (DPOAEs) at 11 frequencies were recorded. Cord and child 6-, 16-, 45-, and 72- month blood samples were analyzed for PCB 153 concentration. The PCB 153 concentration-time profiles were approximated with a system model to calculate area under the PCB*time curves (AUCs) for specific time intervals (3 and 6 months for 45 and 72 months data, respectively). DPOAE amplitudes were correlated (Spearman) with cord serum PCB and AUCs, markers of prenatal and postnatal exposure, respectively. Two exposure critical windows were identified in infants, the first related to prenatal and early postnatal and the second to postnatal exposure to PCBs. Our data have shown tonotopicity, sexual dimorphism, and asymmetry in ototoxicity of PCBs. Highlights: Amplitudes of DPOAE were used as a marker of cochlear status in children. Relations between DPOAEs and perinatal exposures to organochlorines were confirmed. Prenatal exposure to PCB 153 was linked to increased DPOAE amplitudes. Regressions with postnatal PCB exposures indicated poorer DPOAE performance. Any association of serum organochlorines with DPOAE pattern is considered harmful.